2016
DOI: 10.1021/jacs.6b05825
|View full text |Cite
|
Sign up to set email alerts
|

Square-Planar Alkylidyne–Osmium and Five-Coordinate Alkylidene–Osmium Complexes: Controlling the Transformation from Hydride-Alkylidyne to Alkylidene

Abstract: Square-planar alkylidyne and five-coordinate alkylidene mixed (i)Pr3P-Os-IPr (IPr = 1,3-bis(diisopropylphenyl)imidazolylidene) complexes have been discovered and characterized, and their formation has been rationalized. The cationic five-coordinate hydride-alkylidyne compounds [OsHX(≡CPh)(IPr)(P(i)Pr3)]OTf (X = Cl (1), F (4); OTf = CF3SO3) undergo deprotonation with KO(t)Bu to afford the trans-halide-alkylidyne square-planar derivatives OsX(≡CPh)(IPr)(P(i)Pr3) (X = Cl (2), F (5)). Oxidative addition of the C(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 87 publications
(64 reference statements)
4
23
0
Order By: Relevance
“… 33 In 2015, we isolated the five-coordinate hydride-osmium-hydroxy complex [OsH(OH)(≡CPh)(IPr)(P i Pr 3 )]OTf (IPr = 1,3-bis(2,6-diisopropylphenyl)imidazolylidene, OTf = CF 3 SO 3 ), as a result of a chloride by hydroxide replacement. 34 This asymmetrical unsaturated species, supported on an unusual NHC-Os-P i Pr 3 skeleton, 35 possesses three potential reactive points in addition to the metal center: the hydride ligand, the hydroxide group, and the alkylidyne unit. As expected for a hydroxo acid, the hydroxide ligand expresses its duality in the respective nucleophilicity and electrophilicity of the oxygen and hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 In 2015, we isolated the five-coordinate hydride-osmium-hydroxy complex [OsH(OH)(≡CPh)(IPr)(P i Pr 3 )]OTf (IPr = 1,3-bis(2,6-diisopropylphenyl)imidazolylidene, OTf = CF 3 SO 3 ), as a result of a chloride by hydroxide replacement. 34 This asymmetrical unsaturated species, supported on an unusual NHC-Os-P i Pr 3 skeleton, 35 possesses three potential reactive points in addition to the metal center: the hydride ligand, the hydroxide group, and the alkylidyne unit. As expected for a hydroxo acid, the hydroxide ligand expresses its duality in the respective nucleophilicity and electrophilicity of the oxygen and hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it reacts with aldehydes to give carboxylate derivatives and molecular hydrogen. 36 For its part, the osmium−alkylidyne bond undergoes hydroboration and hydrogenation reactions 34,37 as well as insertion into the Os− H bond. 36 The presence of three positions with organometallic reactivity, one of them carrying an oxygen atom, makes the complex an excellent candidate to attempt multicomponent reactions directed toward the synthesis of metallaoxazoles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Os–C(1) bond length of 1.901(3) Å confirms the Os–C double bond. 24 The presence of the hydride ligand in the molecule is also supported by the 1 H NMR spectrum, in dichloromethane- d 2 , at 223 K, which contains a triplet ( 2 J H–P = 21.9 Hz) at −18.54 ppm. In the 13 C{ 1 H} NMR spectrum, the resonance corresponding to C(1) appears at 232.4 ppm.…”
Section: Resultsmentioning
confidence: 77%
“…The reactions for processes involving α-hydrogen migration (X = H) are well-documented and have been observed for a variety of group 6–8 metal complexes . Studies by groups of Esteruelas, Caulton and Stephan have demonstrated that the direction of the transformation can be affected by both metal (M) and ancillary ligands (L). One might expect that the R group may also affect the equilibrium shown in eq , although such an effect has not yet been described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been working on transformations of osmium alkylidene/alkylidyne complexes. In our efforts to study the R effect on α-H migration as well as α-hydrocarbyl migration between osmium alkylidene and alkylidyne complexes, we have searched for a more universal strategy to prepare five-coordinate alkylidene complexes of the type OsCl 2 (alkylidene)­(PR 3 ) 2 , which are still rare in the literature. ,, …”
Section: Introductionmentioning
confidence: 99%